The decrease of simultaneous local election voter turnout in the Lamongan District - Ali Sahab (Faculty of Social and Political Science, Universitas Airlangga, 2018)
Voter turnout in local elections (pilkada) is a participation indicator. The local election in 2015 was diﬀerent from the local elections pre-2015, as the local election in 2015 was held simultaneously. Regional electoral commissions (KPUD) gave candidates campaign facilities like posters, banners, and debates with the other candidates on local television. This socialisation was expected to increase voter turnout. The purpose of this research to ascertain the level of voter turnout in the local election held in 2015 in Lamongan, and whether it is increasing or declining.KPUD has a new role not only to do with socialisation, but KPUD must also print campaign props in line with the fairness principles. The research methods used in this study were a survey and multistage random sampling for the sampling technique. The voter turnout in the 2015 local election was just 60.47% lower than the voter turnout of the 2014 legislative election(Pileg) that reached 71%. In the local election, the emotional bond between the voters and candidates is more powerful than that in a legislativeelection, but in the Lamongan local election 2015, it was not positively correlated. There are two main factors that inﬂuence the decrease of voter turnout. First, is the material orientation of the voters (sangu). If they do not get“Sangu”, they will not vote and they prefer to work in the fields. Voters thought that leaving their job for the election should get them substitution money. Second, was the indication of cartel politics, embracing all political parties in Lamongan Regency, for them to support the same candidate who was still on duty, namely Fadeli, and two other candidates. The level of voter turnout is inﬂuenced by the material orientation of the voters and cartel politics.